The Effect of Ciplukan Fruit Consumption on Hypertension in Pregnancy - Novita Br Ginting Munthe; Iskandar Markus Sembiring (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Pregnancy hypertension is one of the largest contributors to maternal mortality and needs to be alerted and treated immediately, so that it becomes the center of great attention in improving public health. The next problem is that if this condition is not treated immediately, it can progress to more severe conditions, namely preeclampsia and eclampsia, thereby endangering the mother and unborn baby. The risk to the mother can result in permanent and severe brain damage, heart, kidney and liver damage. Meanwhile, babies are at risk of stillbirth, asphyxia, reduced blood flow to the placenta so that the baby can be born prematurely, nutrition to the fetus is disrupted, resulting in the baby being born with a low weight. The aim of the research was to determine the effect of consuming ciplukan fruit on hypertension in pregnancy. This method uses a "quasy experiment" research design with a "pretest-posttest with control group" design. The population in this study were all pregnant women in Lau Rakit Village, STM Hilir District, Deli Serdang Regency, North Sumatra Province. Sampling was carried out by random sampling using the Cluster sampling technique. Time: The research was carried out in July – August 2023. The results of the study showed changes in the systolic and diastolic blood pressure of hypertensive pregnant women after consuming ciplukan fruit. This is shown in the p value results of 0.000 and 0.000 (<0.05). So it can be seen that there is a significant effect of consuming ciplukan fruit on reducing blood pressure in pregnant women who experience hypertension. On the other hand, in the control group, the systolic and diastolic blood pressure of hypertensive pregnant women showed that the p value was 0.095 and 0.133 (>0.05), so it can be concluded that there was no effect before and after measuring the blood pressure of hypertensive pregnant women who did not consume ciplukan fruit. Therefore, pregnancy hypertension can be immediately prevented and treated through traditional or non-pharmacological methods, namely by giving ciplukan (Physialis peruviana) fruit drinks to pregnant women with hypertension.